The near-collapse of LTCM, US financial stock returns, and the fed - Kabir, M.Humayun; Hassan, M.Kabir (Journal of Banking & Finance, 2005)
We examine both the contagion and the “too-big-to-fail” hypotheses in the context of the long-term capital management (LTCM) crisis in the US financial services industry. Our results show that those commercial and investments banks that were exposed to LTCM lost market values significantly around important events surrounding the near collapse of LTCM, but the losses experienced by investment banks are much higher than the losses faced by commercial banks. Smaller S&L institutions and bigger insurance companies were also affected by the crisis, implying a form of contagion effect in the financial sector. We find some evidence of a `too-big-to-fail' policy with the involvement of the Fed in LTCM, as perceived by the markets.